Intersemiosis dan Resemiotisasi dalam Iklan Djarum 76 Berjudul “Jin Online”: Analisis Wacana Multimodal - Sari, Ni Made Dian Paramitha (Jurnal Komunitas Bahasa, 2025)
This study examines the persuasive strategies used in the Djarum 76 "Jin Online" cigarette advertisement, specifically how it navigates strict Indonesian advertising laws that prohibit the direct depiction of smoking. Employing a qualitative, multimodal discourse analysis (MDA) framework, the research investigates the advertisement through the social semiotic concepts of intersemiosis and resemiotization. The analysis utilizes the Visual Grammar for image analysis from Kress and van Leeuwen's Reading Images (2006) and draws on Halliday's Systemic Functional Linguistics (1985) for verbal language data. The core concepts of intersemiosis and resemiotization are grounded in the frameworks developed by O'Halloran (2006) and Iedema (2003), respectively. The primary data is the "Jin Online" video advertisement, which was segmented into 13 scenes for a systematic, scene-by-scene examination of its semiotic modes. Analysis reveals that the advertisement primarily employs a parallel and additive intersemiosis relationship, where verbal and visual modes consistently enrich the overall message. Crucially, the resemiotization process successfully recontextualizes a traditional Javanese genie into a modern, "cool" figure, achieved by strategically reinterpreting and leveraging the cultural popularity of the 2018 online ride-hailing company Gojek including its slogan, ordering process, and the iconic driver's helmet. The advertisement's persuasive force is thus built on the strategic intermodal integration of cultural signifiers to create a desirable identity, effectively bypassing the legal restriction on depicting the product itself.